Basaloid squamous cell carcinoma with adenoid cystic‐like features of the head and neck region: A report of two cases. Issue 10 (15th July 2020) - Kusafuka, Kimihide; Yagi, Haruna; Baba, Satoshi; Inagaki, Hiroshi; Tsuchiya, Chinatsu; Hirata, Kazuki; Muramatsu, Aya; Suzuki, Makoto; Arai, Kazumori; Terada, Tadashi
Abstract : The histology of basaloid squamous cell carcinoma (BSCC) can resemble that of adenoid cystic carcinoma (AdCC). Herein, we report two cases of BSCC with adenoid cystic‐like features (BSCC‐AdC). We collected cases of AdCC and BSCC of the head and neck region, extracted two cases with unusual histology, and reexamined them histologically and immunohistochemically. Case 1 involved an 81‐year‐old Japanese male, who had an elastic‐hard mass on the left side of his tongue, and a biopsy examination suggested AdCC. Case 2 involved a 63‐year‐old Japanese male, who had a polypoid mass on his right hypopharynx. He was diagnosed with AdCC with high‐grade transformation. Histologically, atypical cells in a myxoid stroma, which exhibited trabecular, nest‐like, and/or cribriform growth patterns, and necrosis were observed in both cases. Case 2 displayed more marked cellular atypia than Case 1. Immunohistochemically, the tumor cells were diffusely positive for cytokeratin 5/6, p63/p40, SRY‐related HMG‐box 10 and Ki‐67, but negative for other myoepithelial markers and p16. Finally, both cases were rediagnosed as BSCC‐AdC. It is known that esophageal BSCC displays adenoid cystic‐like features, and BSCC‐AdC also sometimes occurs in the head and neck region. Clinicians should carefully differentiate BSCC‐AdC from AdCC of the minor salivary glands and human papillomavirus‐related carcinoma.